The Alterations of Cortical Volume, Thickness, Surface, and Density in the Intermediate Sporadic Parkinson's Disease from the Han Population of Mainland China - Deng, Xia; Zhou, Meihong; Tang, Chunyan; Zhang, Jie; Zhu, Lei; Xie, Zunchun; Gong, Honghan; Xiao, Xiangzuo; Xu, Renshi (Frontiers in Aging Neuroscience, 2016)
Many symptoms of sporadic Parkinson's disease (sPD) can’t be completely explained by the lesion of simple typical extrapyramidal circuit between striatum and substantia nigra. Therefore, we investigated the alteration of cortical volume, thickness, surface and density in the intermediate sPD from the Han population of Mainland China in order to find the new pathological brain regions associated with the complex clinical manifestations of sPD. The cortical volume, thickness, surface and density were examined using the voxel-based cortical morphometry and corticometry on magnetic resonance image (MRI) in 67 intermediate sPD and 35 controls, the multiple adjusted comparisons analysis of all MRI data were employed to assess the relationships between the cortical morphometric alteration in the specific brain regions and sPD. Results showed that a significantly shrunk volume, thinned thickness and enlarged or reduced surface of cortex in some specific brain regions were closely associated with sPD, but all cortical densities were not different. The majority of morphometric alteration of hemisphere cortex was symmetric, but that in the left hemisphere was more significant. The cortical morphometric alterations in the frontal, temporal, parietal, occipital and limbic lobe, cerebellum, caudate and thalamus were closely related to the clinical neural dysfunction (Clinical manifestations) of sPD. Our data indicated that the deficits of extensive brain regions involved in the development of sPD, resulted in a series of correspondent complex clinical manifestations in the disease.